2021
DOI: 10.1016/j.biopsych.2021.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Corticostriatal Activity Driving Compulsive Reward Seeking

Abstract: Addicts compulsively seek drug rewards. In mice, top down cortico-striatal projections have been implicated in persevering consumption of rewards even when punished. The temporo-spatial determinants of the activity underlying the emergence of compulsive reward seeking however remains elusive. Here we take advantage of a defining 2.7.3 DREADD validation. 2.7.4 eArchT3.0 validation. 2.8 Fibre photometry recordings. 2.9 Acute inhibition of the DS 2.10 Tissue preparation for imaging. 2.11 Statistics 2.12 Clusterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 172 publications
0
20
0
Order By: Relevance
“…It is notably suggested that the transition to compulsion is controlled, in part, by cortico-striatal projections [3,18,22]. This hypothesis is supported by studies demonstrating hypoactivity of the mPFC [67,72] and hyperactivity of OFC projections to the dorsal striatum [76][77][78], leading to an imbalance between these two structures [79] in mice with compulsive-like behaviors. Taken with the present findings, the emergence of the hypodopaminergic state of the nigrostriatal pathway and the imbalance between mPFC and OFC may act in synergy to drive compulsive drug use.…”
Section: Discussionmentioning
confidence: 92%
“…It is notably suggested that the transition to compulsion is controlled, in part, by cortico-striatal projections [3,18,22]. This hypothesis is supported by studies demonstrating hypoactivity of the mPFC [67,72] and hyperactivity of OFC projections to the dorsal striatum [76][77][78], leading to an imbalance between these two structures [79] in mice with compulsive-like behaviors. Taken with the present findings, the emergence of the hypodopaminergic state of the nigrostriatal pathway and the imbalance between mPFC and OFC may act in synergy to drive compulsive drug use.…”
Section: Discussionmentioning
confidence: 92%
“…It is well established that many behavioral functions are specifically regulated by distinct subregions of the PFC. For example, conditioned fear response or trauma (as evidenced in PTSD) is encoded in the ILA 36 , while cue or context-associated reward memory is encoded in PL 37,38 , and compulsive behavior (often associated with drug addiction) is associated with ORBm 39 . Thus, revealing the differential neuron subtype distribution in the different PFC subregions may help link the PFC subregion-specific functions to the various differentially distributed neuron subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Moreover, the adjacent orbitofrontal cortex, which is involved in compulsive behaviors ( 58 ), was not affected by viral infusions targeting the AIC ( SI Appendix , Fig. 3 ).…”
Section: Discussionmentioning
confidence: 99%